A Note on Crawling Along the Ceiling - Matthews, R. C. O. (Review of Economic Studies, 1959)
Journal Article A Note on Crawling Along the Ceiling Get access R. C. O. Matthews R. C. O. Matthews Cambridge Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 27, Issue 1, October 1959, Pages 10–15, https://doi.org/10.2307/2296046 Published: 01 October 1959